2016
DOI: 10.18805/ijar.v0iof.6825
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different extenders on the sperm motilityand viability of frozen Turkey semen

Abstract: This study was conducted to develop long-term storage methods for turkey semen using different extenders. During the study, the massage method was used twice a week to collect the semen from five turkeys, a total of 44 times. The collected fresh semen's average ejaculate quantity, sperm concentration, motility and vitality values were determined as 0.22±0.01 ml, 3.5±0.17 x10 9 sp/ml, 77.0±1.44% and 86.2±0.95 % respectively. In this study, glucose (G) including 5% Dimethyl sulphoxide (DMSO) cryoprotective, tris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
2
4
1
1
Order By: Relevance
“…In a similar study on ducks, as a result of freezing / thawing using 7% DMSO, the lowest vitality value was found as 21.75% and the highest as 32.45% (Setıoko et al, 2002). However, when the vitality and motility values found in studies using 5% DMSO and the same diluents (Kuzlu and Taskin, 2017) on turkeys and 5% DMSO on chickens were compared to the values found in this study, differences were observed. It is thought that these differences may have resulted from the chemical structure of DMSO, the change it made in the diluent used together, and the different stotoxic effect on different poultry spermatozoa (Sexton, 1982).…”
Section: Resultscontrasting
confidence: 65%
“…In a similar study on ducks, as a result of freezing / thawing using 7% DMSO, the lowest vitality value was found as 21.75% and the highest as 32.45% (Setıoko et al, 2002). However, when the vitality and motility values found in studies using 5% DMSO and the same diluents (Kuzlu and Taskin, 2017) on turkeys and 5% DMSO on chickens were compared to the values found in this study, differences were observed. It is thought that these differences may have resulted from the chemical structure of DMSO, the change it made in the diluent used together, and the different stotoxic effect on different poultry spermatozoa (Sexton, 1982).…”
Section: Resultscontrasting
confidence: 65%
“…It was also in the vas deferens where sperm produced by the testicles were stored until the rooster's companion (Salting et al, 2016). These differences may be explained by breed, location, nutrition, age and climate differences because the sperm parameters can vary depending on these factors (Das et al, 2016;Kuzlu and Taskin, 2017;Mavi et al, 2018). As presented in table 2, the percentage of morphologically abnormal spermatozoa in samples retrieved by float-out was 30.33±4.68 % while 30.33±4.68 % abnormality was observed in flushing retrieved samples too.…”
Section: Spermatozoa Retrieved Of the Vas Deferens By Float-out And Fmentioning
confidence: 98%
“…The use of lactated ringer-glucose extender induces higher post-thawing turkey spermatozoa motility when compared to lactated ringer only (Kuzlu & Taskin 2017). According to the study of Mayesta, Trilaksana & Bebas (2014), motility of spermatozoa with 0.6% glucose treatment gave the best results to maintain the motility of Native Rooster spermatozoa on phosphate-egg yolk extenders stored at 3-5 o C. Based on this description the research conducted aims to find the best combination of glucose concentration with the type of extender (lactate ringer egg yolk, lactate ringer skim milk, coconut water egg yolk, and coconut water skim milk) to maintaining progressive motility and viability of Native rooster spermatozoa stored for 48 hours at 5 o C.…”
mentioning
confidence: 94%